Single-handed helical carbonaceous nanotubes prepared using a pair of cationic low molecular weight gelators. (August 2016) - Sun, Huayan; Wang, Qing; Guo, Yongmin; Li, Baozong; Li, Yi; Yang, Yonggang
Graphical abstract: Highlights: 3-aminophenol-formaldeyde resins were prepared through a templating method. A pair of cationic gelators have been used as the templates. Single-handed helical carbonaceous nanotubes were obtained after carbonization. The carbonaceous nanotubes showed optical activity. Abstract: We design a facile route to obtain enantiopure carbonaceous nanostructures, which have potential application as chiral sensors, electromagnetic wave absorbers, and asymmetric catalysts. A pair of cationic low molecular weight gelators was synthesized, which were able to self-assemble into twisted nanoribbons in ethanol at a concentration of 20 g L −1 at 25 °C. Single-handed helical 3-aminophenol-formaldehyde resin nanotubes with optical activity were prepared using the self-assembly of the low molecular weight gelators as templates. After carbonization, single-handed helical carbonaceous nanotubes were obtained and characterized using circular dichroism, wide-angle X-ray diffraction, field-emission scanning electron microscopy, transmission electron microscopy, and Raman spectroscopy. The results indicate that the walls of the nanotubes are amorphous carbon. Moreover, the left- and right-handed helical nanotubes exhibit opposite optical activity.